Reciprocal relationships between sleep quality, mental health and the quality of life in elite athletes: A pilot study - Romdhani, M.; Bentouati, E.; Abid, R.; Moussa-Chamari, I.; Chamari, K.; Saad, H. B.; Driss, T.; Souissi, N. (Biology of Sport, 2026)
We aim to investigate the relationship between sleep quality, psychological health, and quality of life (QOL) in highly trained athletes. Elite athletes (n = 118, 20.1±0.64 years; 39 females; 50 world class; 102 aged * 25 years; and 76 practicing individual sports) responded to the Pittsburgh sleep quality index (PSQI), insomnia severity index (ISI), Epworth sleepiness scale (ESS), Depression, anxiety and stress scale (DASS), world health organization QOL (WHOQOL), and bespoke questions related to sleep hygiene. High percentages of the sample reported low or very low sleep quality (62%), moderate or excessive daytime sleepiness (51%), sleeping 7 hours or less (60%), and moderate or severe insomnia (16%), implying a modest sleep health. Female athletes reported higher PSQI (p < 0.05; d = 0.25), ESS (p < 0.05; d = 0.37) and DASS (p < 0.05; d = 0.27) scores compared to males. Young athletes (i.e., * 25 years) reported higher PSQI (p < 0.05; d = 0.49) and DASS (p < 0.05; d = 0.34) scores compared to older athletes (i.e., > 25 years). Individual-sport athletes reported higher ESS (p < 0.05; d = 0.37) and lower QOL (p < 0.01; d = 0.51) scores compared to team-sport athletes. Higher DASS scores were associated with higher PSQI (t = 3.68; * = 0.3) and ISI (t = 4.78; * = 0.36) scores. Lower physical health (i.e., sub-scale of WHOQOL) was associated with higher DASS (t = -5.01; * = -0.42) and ISI (t = -8.02; * = -0.61) scores. Higher PSQI scores contributed to lower WHOQOL scores (t = -4.81; * = -0.41). In summary, the current study highlights reciprocal relationships between low sleep quality, low mental health and low QOL. Elite athletes (especially sub-groups of female, individual, and young athletes) showed a low sleep quality, potentially affecting their physical and psychological health and QOL.